(untitled) (Research, Society and Development, 2025)
Introduction: Systemic arterial hypertension (SAH) in children has negative implications for cardiovascular health throughout life. Thus, preventive and early diagnostic strategies are essential to reduce the morbidity and mortality associated with this condition, highlighting the importance of proper management from childhood. Objective: To determine the risk factors for the development of childhood SAH in Brazil. Methodology: A systematic review of cross-sectional articles, published from November 2017 to November 2022, was conducted in the electronic databases SciELO, LILACS, and PubMed. The search strategy included the following descriptors in Portuguese: ’Child,’ ’Hypertension,’ ’Risk factors,’ and ’Brazil,’ along with their respective English counterparts. Results: A total of 166 articles were identified, of which five were included. The percentage of children with altered blood pressure levels ranged from 12.3% to 15.5%, with the following associated factors identified: age, place of residence, anthropometric characteristics, eating habits, screen time, and insulin resistance. Conclusion: SAH is a phenomenon present in Brazilian children, influenced by a combination of demographic, anthropometric, dietary, socioeconomic, and behavioral factors. The early identification of children at risk allows for the development of timely interventions, emphasizing the importance of blood pressure measurement in routine pediatric care.